Successfully reported this slideshow.
We use your LinkedIn profile and activity data to personalize ads and to show you more relevant ads. You can change your ad preferences anytime.

Unit2

  1. 1. F ก F 2 ก ก ก ก1. ก F . 6.12. ก F 6.1 .3/1-63. ก F F 3.1 ก ก ก x2+bx+c b c 3.2 ก ก ก ax2+bx+c a≠ 0 a, b c 3.3 F ก ก F 3.4 ก ก ก ก4. F ก F 4.1 / F กF 1) กก ก ก F 1- 4 2) กก ก 1-4 3) กก 4.2 ก F กF 1) ก กก 2) ก F F ก กก ก F 4.3 ก ก F ก F
  2. 2. ก ก F F .3 1 375. ก กก ก ก F F ก F ก5.1 / F กF 1) ก กก - F - ก F F 1- 4 กก 2) ก ก 1-4 3) ก - ก ก - กก กก F F - ก F - F F ก F5.2 ก F กF 1) ก กก - F ก - ก F ก F F ก กก ก F F - F ก F F F - ก F F ก F F - F ก F ก F F 2) ก F F ก - ก ก F ก - ก F F ก กก ก F กก ก F กก ก5.3 ก - - ก - F ก ก
  3. 3. ก ก F F .3 1 38 ก ก F 2/1 ก ก ก x2+bx+c b c 31. ก F 1.1 ก F 1) ก ก x2+bx+c b c F 2) ก F กก ก กF 1.2 Fก F ก ก ก x2+bx+c b c2. 2.1 ก F ก ก ก x2+bx+c b c 2.2 ก /ก ก ก ก F 2.3 ก ก ก ก F ก ก ก ก3. F ก F 3.1 / - กก - กก 3.2 ก ก ก 1) ก F ก F 3 2) ก Fก F 3) Fก F F 4) F ก กก 5) F 6) F ก กก F 7) F
  4. 4. ก ก F F .3 1 39 3.3 ก ก F 1) F F ก ก F 2) ก 3.4 F F ก F ก ก ก x2+bx+c b c F F F ก F4. ก F / /ก ก F F 1) F F 2) F 3) F ก F 80% ก ก F F ก F 3 ก5. ก ก ก ก 5.1 1 F ก (x + 4)(x + 3) F F F F x2+7x+12 2 x +7x+12 = (x + 4)(x + 3) 2 F ก ก ก ก ก F ก ก ก F 1 ก 3 ก ก ก x2+bx+c ก F ก
  5. 5. ก ก F F .3 1 40 5.2 กก ก ก กก 11. F ก (x + 4)(x + 3) F F F F ก กx2+7x+12 x2 + 7x + 12 = (x + 4)(x + 3)2. ก ก F F Fก ก ก F F ก ก F (x + 4)(x + 3) ก ก ก x2+7x+12 ก ก กx2 + bx + c b c ก ก ก F x2+11x+30 ก ก F (x + 5)(x + 6)3. ก ก ก x2+bx+c b c ก ก F F x2+bx+c = (x + p)(x + q) p q ก (x + p)(x + q) = (x + p)x+(x + p)q = x2+px+qx+pq = x2+(p+q)x+pq p+q = b pq = c F F F p q F F ก pq x p q F F4. F F F ก F ก ก ก ก F F ก F ก ก x2+ 14x + 45 ก ก F 2 x + 14x + 45 = (x + .....)(x + .....) F F กก F 14 ก F 45 ก 9 + 5 = 14 9 × 5 = 45 9 5 x2+ 14x + 45 = (x + 9)(x + 5)
  6. 6. ก ก F F .3 1 41 กก ก ก กก5. F ก F ก F ก ก (x + 9)(x + 5) = (x + 9)x+(x + 9)5 = x2+ 9x+5x + 45 = x2+ 14x + 45 ก ก ก ก F6. F ก F ก F ก ก ก ก ก F (1) x2+ 10x + 25 (2) x2+ 12x + 327. F ก Fก F ก F 3-5 F ก F F ก F F ก ก ก ก F F 4 F F ก F 2 F F ก F F ก ก ก F ก F F ก ก ก F Fก F ก F ก ก F F F F ก F ก 21. F 1 ก ก ก ก ก ก ก F ก F F 1 ก ก ก ก ก (1) x2 + 20x + 96 (2) x2 + 6x - 72 ก ก F F F F ก ก (1) ก 12 + 8 = 20 12 × 8 = 96 x2 + 20x + 96 = (x + 12)(x + 8) ก (x + 12)(x + 8) = (x + 12)x+(x + 12)8 = x2 + 12x+8x + 96 = x2 + 20x + 96 ก ก ก ก F
  7. 7. ก ก F F .3 1 42 กก ก ก กก (2) ก (-6) + 12 = 6 (-6) × 12 = -72 x2 + 6x 72 = (x - 6)(x + 12) ก (x - 6)(x + 12) = (x - 6)x + (x - 6)12 = x2 - 6x + 12x - 72 = x2 + 6x - 72 ก ก ก ก F2. ก F ก F ก F ก ก ก ก ก x2 + bx + c FF F กก F F b ก Fc3. F ก กก F 1 F ก ก ก ก F F ก ก F ก F ก ก F 31. ก ก ก x2+ bx + c ก F ก ก ก F ก ก 4 F ก ก F ก F F ก Fก ก ก ก ก FกF F F( F F ก ก Fก F F F ) F F ก F ก 1 3 5 20 30 0 2 4 6 10 50 40 F F F ก2. F 3 ก ก F ก ก F ก ก F F ( F F) F ก ก ก ก F 3 ก ก x2 + x + 10 F x2 + x + 10 = (x + .......)(x + ........)
  8. 8. ก ก F F .3 1 43 กก ก ก กก F กก F 1 ก F 10 ก 1 × 10 = 10 1 +10 = 11 (-1) × (-10) = 10 (-1) + (-10) = -11 2 × 5 = 10 2+5 = 7 (-2) × (-5) = 10 (-2) + (-5) = -7 F F กก F 1 x2 + x + 10 F ก ก F ก F ก ก F3. F ก กก F 2 F ก F ก F ก F ก ก ก ก F ก กF Fก F4. F ก ก 1 ก F ก F 5.3 1) F ก F ก ก 2) F ก F ก ก ก ก x2+bx+c b c 6. ก F/ Fก F 6.1 ก F - 6.2 Fก F - F - F ก F ก F F 7. ก ก 7.1 ก ก F ก F
  9. 9. ก ก F F .3 1 44 F F ก ก F F ก ก ก ก ก x2+bx+c b c F F ก F ก FF F F F F ก F ก F F F ก F ก F F F ก F F F F F F F F F F
  10. 10. ก ก F F .3 1 458. ก ก ก ( ก F ) ก ก F 1. ก กก ก F 2. ก F ก F 3. ก ก F 4. ก ก F ก ก F ก F ก ก F .. F . .. ..
  11. 11. ก ก F F .3 1 469. F ก ก ก กก ก ก ก F ก .................................. ........... ................ ............................. .................... .................................................................. F ก ...................................................................... ก Fก ก F ก ก กก F ก F F ก /ก ก F ก กF ก FF ก F ก F F ก
  12. 12. ก ก F F .3 1 47 ก ก กF ก ก ก .................................. ........... ................ ............................. .................... .................................................................. F ก ...................................................................... ก Fก ก ก F F กกก ก กกก F F ก
  13. 13. ก ก F F .3 1 48 ก ก F 2/2 ก ก ก ax2+bx+c a≠ 0 a, b, c 31. ก F 1.1 ก F 1) ก ก ax2 + bx + c a≠ 0 a, b, c F 2) ก F กก ก กF 1.2 Fก F ก ก ก ax2 + bx + c a≠ 0 a, b, c F2. 2.1 ก F ก ก ก ax2 + bx + c a≠ 0 a, b c 2.2 ก /ก ก ก ก F 2.3 ก ก ก ก ก ก F ก ก3. F ก F 3.1 / - กก - กก 3.2 ก ก ก 1) ก F ก F 3 2) ก Fก F 3) Fก F F 4) F ก กก
  14. 14. ก ก F F .3 1 49 5) F 6) F ก กก F 7) F 3.3 ก ก F 1) F F ก ก F 2) ก 3.4 F F ก F ก ก ก ax2 + bx + c a≠ 0 a, b c F F F ก F4. ก F / /ก ก F F 1) F F 2) F 3) F ก F 80% ก ก F F ก F 3 ก5. ก ก ก ก 5.1 1 Fก ก ก ax2 + bx + c a ≠ 0 a, b, c ก ก ก ก F ก ก F F ก F 2 ก ก ก F ก 3 F ก Fก F F ก F F ก ก ก 2 ax + bx + c a≠ 0 a, b, c
  15. 15. ก ก F F .3 1 50 5.2 กก ก ก กก 11. F ก ก ก ax2 + bx + c ก ก a≠ 0 a, b, c ก ก ก ก F ก ก F F ก F F 2x2 + x - 6 ก ก F F F F F ax2 + bx + c a ≠ 0 กa F x2 กb F x กc F F F ก ก ก ก ax2 + bx + c ax2 + bx + c = (px + r)(qx + s) F ก F (px + r)(qx + s) = pqx2 + psx + rqx + rs = pqx2 + (ps + rq)x + rs FF pq = a ps + rq = b rs = c F p q Fก a r s Fก c F ก ก ps rq Fก b2. F 1 F ก ก ก ก ก ก ก ก F ก ก ก F F ก ก F 1 ก ก 2x2 + x - 6 ก 2( x 2) 2 1 (2x2 + x - 6) (2x........)(x............) ก -6( F F ) F F F x 1
  16. 16. ก ก F F .3 1 51 กก ก ก กก -6 = (-1) × 6 -6 = 1 × (-6) -6 = (-2) × 3 -6 = 2 × (-3) -6 = (-3) × 2 -6 = 3 × (-2) -6 = (-6) × 1 -6 = 6 × (-1) ก (2x - 1)(x + 6), (2x + 1)(x - 6), (2x - 2)(x + 3), (2x + 2) (x - 3),(2x - 3)(x + 2), (2x + 3)(x - 2), (2x - 6)(x + 1), (2x + 6)(x - 1) F (2x - 3)(x + 2) = 2x2 + 4x - 3x - 6 = 2x2 + x 6 2x2 + x 6 = (2x - 3)(x + 2)3. F ก F F ก F ก ก ก F ก ก (1) 6x2 + 4x - 3 (2) 4x2 + 8x + 3 ก F F F ก ก ก F F ก กF Fก F 21. ก ก ก F ก2. F 3 F ก F F F F ก ก F F 3 ก ก 4x2 + 4x - 15 ก ก ก ก F ก 4( x2) 4 = 1×4 2×2 2 F 4x + 4x - 15 (4x............)(x.............)(2x...........)(2x...........) ก -15 ( F F ) F F F x 4
  17. 17. ก ก F F .3 1 52 กก ก ก กก -15 = (-1) × 15 -15 = 1 × (-15) -15 = (-3) × 15 -15 = 3 × (-5) -15 = (-5) × 3 -15 = 5 × (-3) -15 = (-15) × 1 -15 = 15 × (-1) ก (4x - 1)(x + 15), (4x + 1)(x - 15), (4x - 3)(x + 5), (4x + 3)(x - 5), (4x - 5)(x + 3), (4x + 5)(x - 3), (4x - 15)(x + 1), (4x + 15)(x - 1)(2x - 1)(2x + 15), (2x + 1)(2x - 15), (2x - 3)(2x + 5), (2x + 3)(2x - 5), (2x - 5)(x + 3), (2x + 5)(2x - 3), (2x - 15)(2x + 1), (2x + 15)(2x - 1) F (2x + 5)(2x - 3) = 4x2 - 6x + 10x - 15 = 4x2 + 4x - 15 4x2 + 4x 15 = (2x + 5)(2x - 3)3. F ก F ก ก F F F F ก ก ก4. F ก ก 2 F 1 ก F ก F 31. F ก Fก F F ก F F ก ก ก ax2 + bx + c a ≠ 0 a, b c2. ก F F ก F ก Fก กก F F F F F F ก F ก ก F F ก ก F3. F ก ก 2 F 2-4 ก F ก F4. F F ก ก กF F ก F ก F ก ก F
  18. 18. ก ก F F .3 1 53 5.3 F ก F ก ก ก ก ax2 + bx + c a≠ 0 a, b, c6. ก F/ Fก F 6.1 ก F - 6.2 Fก F - F - F ก F ก F F7. ก ก 7.1 ก ก F ก F F F ก ก F F ก ก ก ก ก ax2 + bx + c a≠ 0 a, b, c F FF F ก FF F F F FF F ก F F F ก F ก F F F ก F F F F F F F F F F 7.2 ก ก ก ก ก ก ก F ก F ก F ก ก ก ก ax2 + bx + c a≠ 0 a, b c F ก F F ก ก ก ax2 + bx + c a≠ 0 a, b c ก F Fก ก ก ก ก
  19. 19. ก ก F F .3 1 54 ax2 + bx + c a≠ 0 a, b c F ก ก ก ก ax2 + bx + c a≠ 0 a, b c ก 1. ก ก ก 2. ก ก ก ก ax2 + bx + c a≠ 0 a, b c 3. ก F F F F 4. Fก Fก 1. ก F 2. 3. ก F
  20. 20. ก ก F F .3 1 558. ก ก ก ( ก F ) ก ก F 1. ก กก ก F 2. ก F ก F 3. ก ก F 4. ก ก F ก ก F ก F ก ก F .. F . .. ..
  21. 21. ก ก F F .3 1 569. F ก ก ก กก ก ก ก F ก .................................. ........... ................ ............................. .................... .................................................................. F ก ...................................................................... ก Fก ก F ก ก กก F ก F F ก /ก ก F ก กF ก FF ก F ก F F ก
  22. 22. ก ก F F .3 1 57 ก ก กF ก ก ก .................................. ........... ................ ............................. .................... .................................................................. F ก ...................................................................... ก Fก ก ก F F กกก ก กกก F F ก
  23. 23. ก ก F F .3 1 58 ก ก F 2/3 F ก ก F 51. ก F 1.1 ก F 1) ก ก F ก ก F 2) ก F กก ก กF 1.2 Fก F ก ก ก F ก ก F F2. 2.1 ก F 1) ก ก ก F F ก 2) ก ก ก F ก F 2.2 ก / ก ก ก ก F 2.3 ก ก ก ก ก ก ก ก F3. F ก F 3.1 / - กก - กก 3.2 ก ก ก 1) ก F ก F 3 2) ก Fก F 3) Fก F F 4) F ก กก 5) F
  24. 24. ก ก F F .3 1 59 6) F ก ก ก F ก 7) F 3.3 ก ก F 1) F F ก ก F 2) ก 3.4 F F ก F ก ก ก F ก ก F F F F ก F4. ก F / /ก ก F F 1) F F 2) F 3) F ก F 80% ก ก F F ก F 3 ก5. ก ก ก ก 5.1 1( F ก ) F ก ก ก F 2 2 (1) x - 25 (2) x - 16 (3) x2 36 ก ก F ก ก ก F F F ก F 2( ก ก ) ก ก ก F ก F ก F F F ก ก ก F 3 (ก F) F ก FF ก (x + a)2 = (x + a)(x + a) = x2 + 2xa + a2
  25. 25. ก ก F F .3 1 60 (x - a)2 = (x - a)(x - a) = x2 - 2xa + a2 ก ก กก F F FF F 4 (ก F F) ก ก ก ก F F ก F F ก ก ก 3 F 2 F ก F 5 (ก F F) F F ก ก ก ก ก F F ก F ก F 5.2 กก ก ก กก 1( F ก )1. F ก ก ก F ก ก (1) x2 - 25 (2) x2 - 16 (3) x2 36 ก ก F ก ก F ก ก ก F F F ก F2. F ก ก (x + a)(x - a)(x + a)(x - a) ก F ก F (x + a)(x - a) = (x + a)x - (x + a)a = x2 + ax - xa - a2 = x 2 - a2 ( ก ax - xa = 0) ก F F F x 2 - a2 กF F ก3. F ก F ก ก ก ก FF x2 - a2 = (x + a)(x - a) a4. F ก ก F ก5. ก ก ก F F ก ก F
  26. 26. ก ก F F .3 1 61 กก ก ก กก F ก ก ก ก F 2 2 2(1) x – 16 (2) 4x - 25 (3) x + 16 ก ก F ก ก F ก ก F (1) x2 16 = x2 - 42 = (x + 4)(x - 4) (2) 4x2 25 = (2x)2 - 52 = (2x + 5)(2x - 5) ก ก ก ก F (3) F ก ก ก F F ก F FF F (3) x2 + 16 = x2 + 0x + 16 F ก F 16 กก F 0( ก F F ก F -4 -4 ก F 16 F กก F -8) ก F กF F6. F ก ก ก F (1) x2 - 25 = x2 - 52 = (x + 5)(x - 5) (2) 4x2 16 = (2x)2 - 42 = (2x + 4)(2x - 4) (3) x -36 = x2 - 62 2 = (x + 6)(x - 6)7. F ก ก 3 F 1 ก F ก F 2( ก ก )1. ก ก ก F ก F ก ก F F ก ก ก F ก ก ก ก F ก ก 2 x + 16 F F กF F ( F F กF )
  27. 27. ก ก F F .3 1 62 กก ก ก กก2. ก ก F F Fa F ก ก ก x2 + a2 F F F ก F ก3. ก F ก ก ก F x2 + a2 F x2 + a2 ก F ก ก F Fa F x2 + a24. F ก F ก F ก F 3-5 F F ก F F F ก ก ก F 3-5 F F F F ก F ก F ก F ก ก F ก F F ก ก ก F 3 (ก F)1. F ก F F ก ก ก (x + a)2 = (x + a)(x + a) ก ก F = x2 + 2xa + a2 (x - a)2 = (x - a)(x - a) = x2 - 2xa + a2 ก ก กก F F FF F FF F a x2 + 2xa + a2 = (x + a)2 x2 - 2xa + a2 = (x - a)2 ก F F F x2 + 2xa + a2 = (x + a)2 x2 - 2xa + a2 = (x - a)2 กF ก F ก F F กx F F กa F ก x2 + 2xa + a2 = (x + a)2 ก F Fก ก F F ก F ก Fก F ก F กก2. F 1 2 F ก Fก ก ก ก ก F F 1 ก ก F x2 + 6x + 9
  28. 28. ก ก F F .3 1 63 กก ก ก กก x2 + 6x + 9 F F Fก ก F F ก F ก F x + 6x + 9 = x2 + 2(3) x + 32 2 = (x + 3)2 F 2 ก ก F x2 - 8x + 16 x2 - 8x + 16 F F Fก F F ก F ก F x2 - 8x + 16 = x2 - 2(4)x + 42 = (x - 4)23. F ก F ก F ก ก ก F ก4. F ก ก 3 F 2 ก F ก F 4 (ก F)1. ก ก ก ก F F ก F F ก ก ก 3 F 2 F ก F2. F ก F F ก (ax + b)2 = (ax + b)(ax + b) ก ก = a2x2 + 2axb + b2 (ax - b)2 = (ax - b)(ax - b) = a2x2 - 2axb + b2 ก ก ก ก ก F ก F F F a b F (ax)2 + 2axb + b2 = (ax + b)2 (ax)2 - 2axb + b2 = (ax - b)2 ก F F F (ax)2 + 2axb + b2 = (ax + b)2(ax)2 - 2axb + b2 = (ax - b)2 กF ก F
  29. 29. ก ก F F .3 1 64 กก ก ก กก ก F F ก ax F F ก b F ก (ax)2 + 2axb + b2 = (ax + b)2 ก F Fก ก F F ก F ก Fก F ก F กก F ก ax F F ก b F ก (ax)2 - 2axb + b2 = (ax - b)2 ก F Fก F F ก F ก Fก F F กก3. F 3 F ก Fก ก ก ก ก ก ก F F 3 ก ก ก F F Fก F 2 (1) 4x + 12x + 9 (2) 9x2 - 24x + 16 9 25 (3) x2 + 3x + (4) x2 - 5x + 4 4 2 4x + 12x + 9 F F Fก ก F F ก F ก F 4x2 + 12x + 9 = (2x)2 + 2(2x) 3 + 32 = (2x + 3)24. F ก F ก F ก F5. F ก ก 3 F 3 ก F ก F 5 (ก F F)1. F F ก ก ก ก ก F F ก F ก F F 2 2 (1) x + 4x + 4 (2) x - 12x + 36 (3) 4x2 + 8x + 42. F ก F ก F ก F 3-5 F F ก กก ก 3 F 4 F F ก F F ก ก F F F กF ก ก F ก F3. F ก ก 3 F 5-10 ก F
  30. 30. ก ก F F .3 1 65 5.3 1) F ก F ก ก ก ก F ก 2) F ก F ก 3) F ก F ก ก F 4) F ก F ก ก ก ก ก F6. ก F/ Fก F 6.1 ก F - 6.2 Fก F - F - F ก F ก F F7. ก ก 7.1 ก ก F ก F F F ก ก F F ก ก F ก ก F F F ก F ก FF F F F F ก F ก F F F ก F ก F F F ก F F F F F F F F F F 7.2 ก ก ก F ก ก ก ก F ก F ก F ก ก ก ก ก F
  31. 31. ก ก F F .3 1 66 ก ก ก ก F ก F Fก ก ก ก ก ก F F ก ก ก ก ก ก F ก 1. ก ก ก 2. ก ก ก ก ก 3. 4. F ก ก กก Fก 1. ก F 2. 3. ก F
  32. 32. ก ก F F .3 1 678. ก ก ก ( ก F ) ก ก F 1. ก กก ก F 2. ก F ก F 3. ก ก F 4. ก ก F ก ก F ก F ก ก F .. F . .. ..
  33. 33. ก ก F F .3 1 689. F ก ก ก กก ก ก ก F ก .................................. ........... ................ ............................. .................... .................................................................. F ก ...................................................................... ก Fก ก F ก ก กก F ก F F ก /ก ก F ก กF ก FF ก F ก F F ก
  34. 34. ก ก F F .3 1 69 ก ก กF ก ก ก .................................. ........... ................ ............................. .................... .................................................................. F ก ...................................................................... ก Fก ก ก F F กกก ก กกก F F ก
  35. 35. ก ก F F .3 1 70 ก ก F 2/4 ก ก ก ก 31. ก F 1.1 ก F 1) ก ก ก F F 2) ก F กก ก กF 1.2 Fก F ก ก ก ก F F2. 2.1 ก F ก ก ก ก 2.2 ก / ก ก ก ก F 2.3 ก ก ก ก ก ก F ก ก3. F ก F 3.1 / - กก - กก 3.2 ก ก ก 1) ก F ก F 3 2) ก Fก F 3) Fก F F 4) F ก กก 5) F
  36. 36. ก ก F F .3 1 71 6) F ก กก F ก 7) F 3.3 ก ก F 1) F F ก ก F 2) ก 3.4 F F ก F ก ก ก ก F F F F ก F4. ก F / /ก ก F F 1) F F 2) F 3) F ก F 80% ก ก F F ก F 3 ก5. ก ก ก ก 5.1 1 ก FFก ก ก n ก 2 ก F ก F F ก ก ก 4 F 1 F ก F FF F ก F F ก กF Fก F 3 F 6 F ก F ก ก F 6 ก ก x4 + 3x3 - 7x2 - 27x 18
  37. 37. ก ก F F .3 1 72 5.2 กก ก ก กก 11. ก FFก ก ก n ก ก ก anxn + an-1xn-1 + an-2xn-2+ ... + a0 ก F ก n n an F F ก F an, an-1, an-2, ..., a0 F กF ก ก F F ก ก ก F ก F F x3 + 4x2 - 6x - 20 ก 3 a3 = 1, a2 = 4, a1 = -6 a0 = 202. F ก ก F ก ก ก F(x3 + 4x2 - 6x - 20) ÷ (x + 2) ก ก x2 + 2x - 10 x + 2 x3 + 4x2 - 6x - 20 3 2 x + 2x 2x2 - 6x 2x2 + 4x - 10x - 20 - 10x - 20 0 ก ก F ก F F ก F( ) ก F Fก F F ก F x3 + 4x2 - 6x 20 = (x + 2)(x2 + 2x - 10) ก F F F P(x) Q(x) FF F ก P(x) = (x + 2)Q(x) .. (1) ก x F -2 ก (1) F P(-2) = (- 2+ 2)Q(-2) = 0[Q (-2)] = 0
  38. 38. ก ก F F .3 1 73 กก ก ก กก F ก F ก F F F F ก FF ก F ก ก P(x) F x + 2 F x F -2 F P(-2) = 0 ก3. F ก ก F ก ก ก F 3 2 (x + 4x - 6x - 16) ÷ (x + 2) ก ก x2 + 2x - 10 x + 2 x3 + 4x2 - 6x - 16 x3 + 2x2 2x2 - 6x 2x2 + 4x - 10x - 16 - 10x - 20 4 ก ก กก Fก F F ก F FF F Fก F F ก F FF x + 4x - 6x - 16 = (x + 2)(x2 + 2x - 10) + 4 3 2 ก F F F P(x) Q(x) F P(x) = (x + 2)Q(x) + 4 (2) ก x F -2 ก (2) F P(-2) = (- 2+ 2) Q(-2) + 4 = (0)Q(-2) + 4 = 0+4 = 4 F ก P(x) F x + 2 F 4 x F -2 F P(-2) = 4 ก ก F Fก F F กF
  39. 39. ก ก F F .3 1 74 กก ก ก กก F P(x) (x - c) Q(x) R(x) ก R(x) ก F F F P(x) = (x - c)Q(x) + R(x) F x - c P(x) F F P(c) = R(c) = 0 F x - c P(x) F F P(c) = R(c) F Fก F ก4. F 1 F ก F ก ก ก ก ก F 1 x-2 F x3 + 2x2 - 5x - 6 F F ก ก ก ก ก F F F ก 2 1 Fก F x2 + 4x + 3 x - 2 x3 + 2x2 - 5x - 6 x3 - 2x2 4x2 - 5x 4x2 - 8x 3x - 6 3x - 6 0 x - 2 x3 + 2x2 - 5x - 6 F 2 F F P(x) = x3 + 2x2 - 5x - 6 P(x) F x - 2 ก F 2 P(x) F P(2) = 23 + 2(2)2 5(2) - 6 = 8 + 8 - 10 - 6 =0 x3 + 2x2 - 5x - 6 F x-2 F5. ก F 2 F ก F F ก F ก
  40. 40. ก ก F F .3 1 75 กก ก ก กก (x - c) P(x) = anxn + an-1xn-1 + an-2xn-2+ ... + a0 F c F F ก a0 F ก an6. F ก ก 4 F 1 F ก F ก F 21. ก F ก F F ก ก ก 4 F 1 F ก F FF F ก F F ก กF Fก F2. F 3 F ก ก ก ก F F 3 F x - c x3 - 2x2 - 5x + 6 F F c F F ก ก F ก ก x3 - 2x2 - 5x + 6 ก x3 1 a0 6 F c FF ก 6 ก 6 F กF ±1, ±2, ±3, ±6 ก P(x) ก 3 F c F Fก 3 F F P(x) = x3 - 2x2 - 5x + 6 c F 1 F P(1) = 1 - 2 - 5 + 6 =0 (x - 1) x3 - 2x2 - 5x + 6 F c F -2 F P(-2) = (-2)3 - 2(-2)2 - 5(-2) + 6 = -8 - 8 + 10 + 6 =0 {x - (-2)} = x + 2 x3 - 2x2 - 5x + 6 F c F 3 F P(3) = (3)3 - 2(3)2 - 5(3) + 6 = 27 - 18 - 15 + 6 =0
  41. 41. ก ก F F .3 1 76 กก ก ก กก x -3 x3 - 2x2 - 5x + 6 c 1, -2 3 ก ก x3 - 2x2 - 5x + 6 F (x - 1)(x + 2)(x - 3)3. F ก Fก F 3ก F F F F F ก F F F ก F Fก F 4-5 F F F F ก F Fก F F ก F F F ก F ก F ก F F ก F 1 F F F ก F ก F4. F ก Fก F5. F 4 F ก ก ก F F 4 ก ก x3 - 19x + 30 ก ก ก ก F FF F F ก F F ก ก F ก ก F FF ก F F F ก F F ก F P(x) = x3 - 19x + 30 ก F c FF ก 30 ก 30 F กF ±1, ±2, ±3, ±5, ±6, ±10, ±15, ±30 F c F Fก 3 F ก P(2) = 23 - 19(2) + 30 = 8 - 38 + 30 =0 (x - 2) x3 - 19x + 30 F
  42. 42. ก ก F F .3 1 77 กก ก ก กก x3 - 19x + 30 = (x - 2)(x2 + 2x - 15) = (x - 2)(x - 3)(x + 5)6. F ก ก ก F ก F 3-5 F F ก F F ก ก ก ก F ก Fก F F F กก F ก F ก F F(1) x3 + 6x2 - 11x + 6 (2) x3 + 6x2 - 32 (3) x3 + 4x2 + x - 6 31. F 6 F ก F ก ก F 6 ก ก x4 + 3x3 - 7x2 - 27x - 18 ก F 6 ก F F P(x) = x4 + 3x3 - 7x2 - 27x - 18 ก F c F F ก 18 ก 18 F กF ±1, ±2, ±3, ±6, ±9, ±18 F c F Fก 4 F ก P(-1) = (-1)4 + 3(-1)3 - 7(-1)2 - 27(-1) - 18 = 1 - 3 - 7 + 27 - 18 =0 (x + 1) x4 + 3x3 - 7x2 - 27x 18 F
  43. 43. ก ก F F .3 1 78 กก ก ก กก x4 + 3x3 - 7x2 - 27x - 18 = (x + 1)(x3 + 2x2 - 9x - 18) (1) F Q(x) = x3 + 2x2 - 9x - 18 ก Q(-2) = (-2)3 + 2(-2)2 - 9(-2) - 18 = - 8 + 8 + 18 - 18 = 0 3 2 (x + 2) x + 2x - 9x - 18 F x3 + 2x2 - 9x 18 = (x + 2)(x2 - 9) = (x + 2)(x + 3)(x - 3) .. (2) ก (1) (2) FF x4 + 3x3 - 7x2 - 27x - 18 = (x + 1)( x3 + 2x2 - 9x - 18) = (x + 1)(x + 2)(x + 3)(x - 3)2. F ก ก 4 ก F ก F 5.3 1) F ก F ก ก ก ก 2) F ก F ก ก ก ก ก F 6. ก F/ F ก F 6.1 ก F - 6.2 F ก F - F
  44. 44. ก ก F F .3 1 79 - F ก F ก F F7. ก ก 7.1 ก ก F ก F F F ก ก F F ก ก ก ก ก ก F FF F ก FF F F F FF F ก F F F ก F ก F F F ก F F F F F F F F F F 7.2 ก ก ก -
  45. 45. ก ก F F .3 1 808. ก ก ก ( ก F ) ก ก F 1. ก กก ก F 2. ก F ก F 3. ก ก F 4. ก ก F ก ก F ก F ก ก F .. F . .. ..
  46. 46. ก ก F F .3 1 819. F ก ก ก กก ก ก ก F ก .................................. ........... ................ ............................. .................... .................................................................. F ก ...................................................................... ก Fก ก F ก ก กก F ก F F ก /ก ก F ก กF ก FF ก F ก F F ก
  47. 47. ก ก F F .3 1 82 ก ก กF ก ก ก .................................. ........... ................ ............................. .................... .................................................................. F ก ...................................................................... ก Fก ก ก F F กกก ก กกก F F ก
  48. 48. ก ก F F .3 1 83 ก F ก F ก F 2 (Self Reflection) 1. ก F F ก 1.1 ก F F ก F กF F ก F F ก F Fกก ก F F F 1.2 F ก กก F F F กก F F ก F 2 / / ก ................ /................ /................ ก ก 1. กก F F F F .. . .. . 2. F F F .. . .. . 3. F F Fก F F F F .. . .. . 4. F กก .. . .. . 2. ก ก ก Fก ก1. ................................................................................................................................................ .. .
  49. 49. ก ก F F .3 1 84 ....................................................................................................................................................... .. . ............................................................................................................................................... ... .. . .............................................................................................................................................. .... .. . ก กF .............................................................................................................................................. .... .. . .. .2. F ก กF 2.1 กF ............................................................................................................. .. ก ..................... F ................ ................. F.......................... ................................................................................................................................................ 2.2 ก ก กF ก ก .................................................................................... ................................ ก F F กF ................................................. ................................................................................................................................................ 3. ก กF 3.1 ก F ก กF ก ............................. F .................. .................. ....................... ก ก ....................... ก ก ................................................................................................................................................ 3.2 F ก ก .................................. F ก F ............................. ......................................................................................................................................... 3.3 ก ก ......... F/ F .......... ....................... . . ..................... .......... .......................... . . .......................4. ก ก กF 4.1 F ก กF ..................................................................................................................................................... .....................................................................................................................................................
  50. 50. ก ก F F .3 1 85 ก F ....................................................................................................................................................... ....................................................................................................................................................... ....................................................................................................................................................... 2.2 F ก ก F ....................................................................................................................................................... ....................................................................................................................................................... ก F ....................................................................................................................................................... ....................................................................................................................................................... ....................................................................................................................................................... 2.3 ก ก F F ก ก F ก 1) F ก กF Fก ก ........................................................................................................................................... .......................................................................................................................... .......................................................................................................................................... 2) ก F ก F ก ก ........................................................ ... ......................................................................................................................... ...... 2.4 ก FF ก F ก F F .. .. ..5. ก กF ก กF ก ก ................................................................................................................ ก ก F ก ........................................................................................................................................................ ..................................................................................................................................................... ....................................................................................................................................................... ...

×